IMPACT OF UNDELIMITED AREA IN THE MALACCA STRAIT ON INDONESIA-MALAYSIA RELATIONS - Bambang Subeno; Muhammad Syaroni Rofii (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2022)
Indonesia has a border dispute in the Malacca Strait with the neighboring country, Malaysia, which results in undelimited waters areas. This research aims to analyze the impact of Indonesian government policies on Malaysia related to undelimited waters in the Malacca Strait according to the Theory of Sovereignty. This study is a qualitative study that uses a case study approach. The data obtained from the literature study came from several scientific articles and government documents, interviews with several informants, and direct observations of the object under study. In this research, the level of problems will be seen through the impact of incidents in undelimited waters in the Strait of Malacca on Indonesia-Malaysia relations. The incident is already at an alarming stage because there have been clashes that threaten the safety of ships and lives, that might cause conflict/use of violence, and threaten bilateral relations. This study found that the priority of the Government of Indonesia's policy in upholding sovereignty in border areas in Indonesia is carried out using a security and community welfare approach. To minimize incidents that occur between the two countries in overlapping areas, bilateral relations are enhanced through coordinated patrols